Self-compassion and work engagement among clinical nurses: the mediating role of moral resilience - Liu, Xingxing; He, Fang; Tian, Tian; Zhang, Jun; Ji, Yuanjiao; Zhong, Yuexia (Frontiers in Public Health, 2025)
BackgroundAs the workload of clinical nursing continues to increase, the mental health of nurses has emerged as a critical area of concern. Self-compassion, moral resilience, and work engagement are essential components in enhancing the mental health of clinical nurses. Although it is well-established that self-compassion significantly contributes to improved work engagement, there remains a notable lack of research investigating the specific mechanisms through which self-compassion influences work engagement, particularly from the perspective of moral resilience. This study aimed to address this gap by examining the relationships among self-compassion, moral resilience, and work engagement in clinical nurses, while also validating the mediating role of moral resilience in the relationship between self-compassion and work engagement.MethodsThis study utilized a convenience sampling method to conduct a cross-sectional online survey involving 844 clinical nurses from four tertiary A hospitals in Xi’an, China, between January and March 2024. Participants completed self-report questionnaires that included the Self-Compassion Scale, the Rushton Moral Resilience Scale, and the Utrecht Work Engagement Scale. The data analysis involved descriptive statistics, the Mann–Whitney U test, the Kruskal-Wallis H rank-sum test, Spearman correlation analysis, and the SPSS PROCESS macro.ResultsA significant positive correlation was observed between clinical nurses’ self-compassion and moral resilience (r = 0.700, p < 0.01). Additionally, a significant positive correlation was identified between self-compassion and work engagement (r = 0.455, p < 0.01). Furthermore, there was a significant positive correlation between moral resilience and work engagement (r = 0.510, p < 0.01). Mediation analysis indicated that moral resilience partially mediates the relationship between clinical nurses’ self-compassion and work engagement. The overall effect of self-compassion on work engagement (β = 0.493) consists of both a direct effect (β = 0.251) and an indirect effect mediated by moral resilience (β = 0.242). Notably, the mediating effect accounts for 49.09% of the total effect.ConclusionClinical nurses’ moral resilience plays a mediating role in the relationship between self-compassion and work engagement. Nursing managers should prioritize fostering and enhancing the self-compassion and moral resilience of clinical nurses to effectively elevate their levels of work engagement. These targeted interventions can ultimately improve not only the mental health and professional well-being of nurses but also the overall quality of care delivered in medical institutions.